Combination of FOBIO biopesticide and Brassica rapa L. as remediator of heavy metal Pb in soil - Surya Ari Widya; Moch. Arifin; Sri Wiyatiningsih (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
Marginal soil is infertile soil caused by various factors, one of which is the excessive accumulation of heavy metals. FOBIO microorganism-based biopesticide formula containing phosphate solubilizing bacteria is expected to be used to reduce excess heavy metals in the soil. Brasica rapa L. is a variety resistant to Pb heavy metal stress and absorbs more heavy metals into root tissue than leaf tissue with the help of microorganisms. This study aimed to determine the combination of Brassica rapa L. and FOBIO biopesticide in absorbing Pb in the soil, determine the growth of Brassica rapa L. at each Pb concentration, and determine the population of phosphate-solubilizing bacteria in the soil at each level of Pb stress after remediation. This study used variations in the concentration of heavy metals, particularly Pb. Parameters observed included plant growth, Pb concentration in the soil before and after remediation, and the population of phosphate-solubilizing bacteria. The results showed that combining FOBIO biopesticides and Brassica rapa L. could reduce Pb concentration in the soil. The growth of Brassica rapa L. plants was significantly different after treatment. The findings confirmed that increasing, the concentration of Pb led to a decrease in the population of phosphate-solubilizing bacteria.